Treatment Of Rhodamine B And Acid Red 18 By Electrocoagulation Using Iron Electrode - Zulkifli, Muhammad Akmal (Universiti Sains Malaysia, 2018)
The electrocoagulation (EC) process is an electrochemical process that introducing coagulants and removing suspended solids, colloidal materials, metal, and other dissolved solids from wastewaters. In this study, Acid Red 18 (AR18) and Rhodamine B (RhB) are used as synthetic wastewater. The parameter involved in this study are initial concentration of dye solution, current density and electrocoagulation time. The process efficiency of EC was determined by percentages removal of colour and chemical oxygen demand (COD). It was found that the increasing initial concentration will reduce removal efficiencies for both dyes solutions. Meanwhile, optimum current density which is 50A/m2 will increase the efficiencies of colour with 95% for AR18 and 70% for RhB and COD removal with 83% for AR18 and 43% for RhB. For EC time variables, the optimum time of treatment for AR18 is 1 hour, while optimum time for RhB is 2 hours with efficiencies 91% and 87% respectively.